Enhancing reading comprehension through cognitive and graphic strategies: a constructivism approach - Mohd Yussof, Yusfarina; Jamian, Abdul Rasid; Roslan, Samsilah; Zainon Hamzah, Zaitul Azma; Kabilan, Muhammad Kamarul (Elsevier, 2012)
Graphic Strategy and several Cognitive Strategies (Story Structure, Questioning, Synthesizing, Visualizing and Inferencing) are used on narrative texts, following constructivism principle, to discern the increase in students’ reading comprehension.A quasi-experimental study involved 45 students(experimental group) receiving treatment via graphic and cognitive strategies and another 45 students (control group) using classroom's common practice (conventional method). Paired T-test Analysis shows significant difference for both groups. However, mean score and effect size (eta square value) are larger in the experimental group (M=59.63, 0.78) than the control group's (M=55.34, 0.31). This indicates that the implemented strategies increased students’ reading comprehension effectively compared to conventional method.